Upaya meningkatkan keterampilan passing permainan futsal menggunakan latihan drill pada peserta ekstrakurikuler SMK Texmaco Purwasari - Rojabi, Fakhri Ahmad; Yuda, Aria Kusuma; Nugroho, Setio (Jurnal Porkes, 2024)
This study aims to examine the effect of the drill training method on efforts to improve passing skills in futsal games. The method used in this research is quantitative with experimental method and type of one group pretest and posttest. The population in this study were 14 people and used total sampling. The instrument used in this study is a type of skill test instrument. The data analysis technique used in this study is using SPSS. The results of the Levene statistical value are 0.069 to 0.212, with the lowest significance value of 0.649 and the highest of 0.795. The pretest data, the Lilliefor statistical value is 0.157 with a significance of 0.200. The calculated t value is -3.277 with a degree of freedom (df) of 13 and a significance value (2-tailed) of 0.006. This significance value is smaller than the standard alpha level of 0.05, which means that the difference between the pretest and posttest is statistically significant. This is evidenced by a significant increase in the average passing skill from 6.29 in the pretest to 7.64 in the posttest, as well as an increase in the minimum value from 4 to 6. A decrease in standard deviation from 1.326 to 1.082 and variance from 1.758 to 1.170. It is concluded that the application of the drill training method is an effective strategy to improve passing skills in futsal games.